Macromineral, micromineral and metal concentration of bovine colostrum samples from Salzburg, Austria - Katharina Lichtmannsperger; Nicole Hechenberger; Ariane Psenner; Maren Marseiler; Andrea Hildebrand; Elisabeth Müller; Alexander Tichy; Thomas Wittek (Journal of Trace Elements and Minerals)
Background: Besides immunoglobulins which are essential for the calf to prevent Failure of Transfer of Passive Immunity (FTPI) colostrum contains multiple other constituents such microminerals, macrominerals and metals. The concentration of the minerals seems to be higher in colostrum than in normal milk. The aims of this study were to describe macromineral, micromineral and metal concentration of bovine colostrum samples from Salzburg, Austria and to see if there are differences in the concentrations between different cow feeding strategies and farm locations. Methods: Therefore, 1050 individual colostrum samples were collected from 72 dairy farms from different districts of Salzburg. All colostrum samples were analysed for macromineral (K, Mg, Na), micromineral (Co, Cu, Fe, I, Mg, Se, Zn) andmetal (As, Ba, Cd, Li, Mo, Ni, Pb, Sr, Tl, U) concentrations by inductive coupled plasma mass spectrometry. Results: The mean K, Mg and Na levels were 1218.71 mg l-1, 245.44 mg l-1 and 358.62 mg l-1, respectively. The micromineral concentrations of I, Se, Co and Zn were significantly higher in colostrum from dairy cows feeding a Total-Mixed-Ration during the lactation period in comparison to cows receiving microminerals by hand feeding, transponder feeding or via a licking bucket or licking stone. The metal analysis showed that in three farms, most of the colostrum samples showed Pb levels above the limit of 5 µg l-1. Implications: Herd-level factors need to be addressed to elevate micromineral concentrations and to reduce metal concentrations in colostrum from dairy cows from Salzburg, Austria. Conclusion: The results show that the macrominerals K, Mg and Na are within the range of published concentrations. For the microminerals, Co, Cu, Fe, I, Mg, Se and Zn the concentrations were significantly different depending on the mineral feeding strategies during the lactation and dry period. Metal concentrations of As, Ba, Cd, Li, Mo, Ni, Pb, Sr, Tl and U differed between the districts of Salzburg.